Helium migration and precipitation in irradiated and annealed copper boron alloy - Tiwari, Gyanendra P.; Mishra, Ratikanta; Mehrotra, Radhey Shyam (Diffusion Fundamentals, 2013)
The paper analyses afresh the data of Russell and Hastings on the changes in lattice parameter during post-irradiation annealing of copper-boron alloy in the temperature range 823-923 K. The changes in lattice parameter are brought about by the generation of helium during irradiation through (n, α) reaction and its subsequent behavior during annealing. The new analytical procedure adopted here follows chemical kinetics route to determine the appropriate activation energies associated with the rate processes controlling the changes in lattice parameter. During the first stage of annealing, the lattice parameter decreases to a value which is below the equilibrium one. The second stage involves the recovery of lattice parameter to the equilibrium value. The diffusion of monovacancy and the jump of helium atom to vacancy on its nearest neighbor site are identified as the unit processes for the first and second stages of annealing respectively. Finally, it is suggested that a helium–monovacancy complex may act as nucleus for the formation of helium gas bubbles.